Educational Values of Roadside Trees in Carcar City, Cebu, Philippines: Implications to Environmental Education - Joje Mar Perino Sanchez; Aila Louella Marie I. Teologo; Rhona R. Villamejor; Grazen Brithzel T. Rieta; Jeanne S. Oberes; Jessa O. Romeo; Zandher Austin D. Pahamotang; Shervi A. Gempisao; Lenylyn E. Villarojo (Biosaintifika: Journal of Biology & Biology Education, 2021)
Roadside trees along the national highway in Barangay Perrelos in Carcar City are trees that considered a heritage, and yet are affected by urban developments in the province. The study determined the profile of the roadside trees as well as the knowledge, attitudes, and conservation efforts of the locals in the area. Questionnaires and interviews were given to 50 respondents, and data gathered were analyzed using ANOVA, Pearson r and thematic analysis. Ecological indices such as abundance percentage and species richness were also used by the study. Results revealed that there are 108 identified roadside trees, where the species richness is 0.962 and acacia trees are the most abundant (46.30%). Knowledge and attitudes of the respondents were high and low-to-moderate, respectively. Conservation practices towards the roadside trees included pruning, no burning near the trees and making of diversion roads, all adhering with existing environmental laws of the country. Tree abundance and richness, knowledge acquisition, attitude inculcation, and conservation efforts are manifestations of the educational values of roadside trees to the people. Research on these educational values of trees is novel as it provides importance on cultural heritage, environmental protection, and sustainable planning in the area. Implications to environmental education are formulated for the Philippine elementary and secondary education Science teaching.